Mobilitas Sosial dan Praktik Keagamaan: Dampak Pembangunan Infrastruktur (Pelabuhan) terhadap Struktur Masyarakat Nelayan Tradisional di Pulau Bengkalis (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
Infrastructure expansion has been increasingly recognized as a transformative force shaping the social, economic, and cultural dynamics of coastal communities. This study investigates the effects of major infrastructure development specifically ports and toll roads on social mobility and religious practices within the traditional fishing communities of Bengkalis Island. Using a qualitative design, data were collected through field observations, in-depth interviews with fisherfolk, local leaders, and religious figures, as well as reviews of regional development policies. The findings reveal that new infrastructure has introduced shifts in livelihood patterns, encouraging economic diversification beyond traditional fishing activities. These shifts contribute to both upward and horizontal mobility, altering long-standing social hierarchies within the community. Moreover, the changing economic landscape influences religious life: traditional maritime rituals experience reduced centrality, while formalized religious organizations gain greater authority and participation. Infrastructure development also increases exposure to external cultural influences, accelerating negotiations of religious identity and modern interpretations of faith. Overall, this study argues that infrastructure projects function not only as physical catalysts of development but also as sociocultural drivers that reshape belief systems, communal relations, and the lived realities of traditional fishing populations. The research highlights the necessity of adopting development strategies sensitive to local contexts and cultural continuity.